The Promise of Cultural Diplomacy - Hedda Krausz Sjögren; Kristina Hagström-Ståhl (The Thinker)
This article offers a reflection on the potentials of cultural diplomacy and cooperation, situating itself in the long-term relationship between South Africa and Sweden as well as the specific context of the professional practice of Sweden’s first counsellor for cultural affairs in South Africa, Hedda Krausz Sjögren. Providing a first-hand account of cultural diplomacy, it adopts a self-reflexive position and, largely, a first-person perspective. Co-authored by Krausz Sjögren and one of her collaborators during this period, a theatre director and researcher, Kristina Hagström-Ståhl, it also attempts to reflect the shared experience of collaborative work in this sphere. As such, the text is written from within a combination of diplomatic, cultural, and professional practices, as well as from within a diverse set of skills informing the practices that shaped the body of work to which the article refers. We use a combination of personal and collective pronouns throughout this article to place emphasis on our reflections; the use of personal pronouns denotes Krausz Sjögren’s reflections. We aim to share a sense of the possible impact of work dedicated to democracy, freedom of expression, and gender inclusion.